2001
DOI: 10.4049/jimmunol.167.4.2193
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiTachyzoites Inhibit Proinflammatory Cytokine Induction in Infected Macrophages by Preventing Nuclear Translocation of the Transcription Factor NF-κB

Abstract: Control of microbial infection requires regulated induction of NF-κB-dependent proinflammatory cytokines such as IL-12 and TNF-α. Activation of this important transcription factor is driven by phosphorylation-dependent degradation of the inhibitory IκB molecule, an event which enables NF-κB translocation from the cytoplasm to the nucleus. In this study, we show that intracellular infection of macrophages with the protozoan parasite Toxoplasma gondii induces rapid IκB phosphorylation and degradation. Neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
192
8
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(217 citation statements)
references
References 62 publications
13
192
8
4
Order By: Relevance
“…However, within the next phase of activation, HSP70 levels are sufficient to reduce NF-B uptake to the nucleus. This timing fits very nicely with the timings of suppression of immune activities observed by Butcher et al (13). Furthermore, our observation that the inhibition of NF-B translocation was not complete (an observation also made by Butcher et al, Ref.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, within the next phase of activation, HSP70 levels are sufficient to reduce NF-B uptake to the nucleus. This timing fits very nicely with the timings of suppression of immune activities observed by Butcher et al (13). Furthermore, our observation that the inhibition of NF-B translocation was not complete (an observation also made by Butcher et al, Ref.…”
Section: Discussionsupporting
confidence: 76%
“…This activity could result in prevention of I B phosphorylation and subsequent dissociation of NF-B. However, this explanation seems unlikely to account for the effect of T. gondii HSP70, because it has recently been shown that although tachyzoites do invade macrophages without activating NF-B, they trigger normal phosphorylation-dependent degradation of I B, thus indicating that the block on NF-B translocation occurs downstream of these events (13).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, despite the initiation of NF-B signaling, infection with T. gondii did not lead to the activation of NF-B but to its termination. The reason for disabling NF-B is associated with blocking of p65 translocation to the nucleus (10,12,13). Other studies have demonstrated that T. gondii activates NF-B, which up-regulates the expression of anti-apoptotic genes to facilitate the replication of the pathogen (15)(16)(17).…”
mentioning
confidence: 99%
“…This observation demonstrated the importance of NF-κB p65 component as a key factor in the protection of the infected fibroblast against apoptosis [99]. It should be noted, however, that movement of NF-κB to the nucleus is not observed in all types of infected cells including macrophages, which do not exhibit NF-κB translocation early after invasion [105][106][107]. This may be due to inherent differences between cell types or a result of examining translocation at different time points post-invasion.…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 82%